Investigation of Marshall Properties of HMA Rubberised Asphalt Mixture - Zahari, Muhammad Hazrul Izzat (Recent Trends in Civil Engineering and Built Environment, 2026)
Asphalt pavements are critical components of contemporary transportation infrastructure, providing long-lasting and cost-effective road surfaces. Traditional asphalt mixtures, on the other hand, are prone to cracking, rutting, and ageing, resulting in early pavement deterioration. Alternatively, researchers have investigated the use of crumb rubber obtained from recycled tyres in asphalt mixes. This study aims to determine the ideal proportion of crumb rubber in the asphalt mixture in order to produce mechanical features such as higher resistance to cracking and rutting, increased durability, and decreased environmental effect. The Marshall stability, flow, air voids, bulk density, and indirect tensile strength of asphalt mixes are among the key factors researched. This study’s results add to a better understanding of the impact of bitumen content on the performance of gap-graded HMA mixes with crumb rubber. The findings may be utilized to improve bitumen concentration in future mix designs while keeping desirable performance criteria and environmental factors in mind. Furthermore, the research sheds light on the viability of using crumb rubber as a sustainable addition in asphalt pavement construction, increasing waste material reuse and lowering the environmental effect of the transportation industry.